(untitled) (Research, Society and Development, 2020)
Rectal prolapse a rectal static disorder and is more common in donkey than in horses. The aim of this study was to relate the cases of three type II retained prolapses in northeastern donkeys (Equus asinus) that were vulnerable and mistreated, from the exploratory chain to decrease. Two males and one female, which were treated, exhibited an evolution of prolapse over 6, 24, and 96 h. Tachycardia and tachypnea were observed in the two cases with the shortest duration of prolapse evolution, for which conservative mechanical reversal was effective, without the need for a surgical procedure. Conditions differed between the heart rate and respiratory parameters in case with 96 h of evolution, or in those where it was necessary to use epidural anesthesia and sphincter suture with a tobacco bag pattern. The findings of this study reinforce the need to compile cases from the literature to establish a standard protocol for rectal prolapse in donkeys.